KAJIAN KONDISI PERKERASAN LENTUR DAN PENENTUAN TINDAKAN PEMELIHARAAN MENGGUNAKAN METODE PCI - Misbah Misbah; Malvin A. Rachman; Hendri Nofrianto; Meli Muchlian (Ensiklopedia of Journal, 2026)
Road surface damage has a direct impact on service quality and user safety. This study aims to assess the type and extent of flexible pavement damage and to develop maintenance recommendations using the Pavement Condition Index (PCI) method. The case study was conducted on a 2 km section of Soekarno-Hatta Road in Sungai Penuh City, Jambi Province (STA 0+000–2+000), which serves a vital role as a connector between urban areas, tourist sites, and inter-provincial networks. Data collection involved a visual inspection through a walkthrough survey of 40 observation segments. The survey identified 14 types of damage, with longitudinal cracks, potholes, alligator cracks, and local subsidence being the most prevalent. The PCI values revealed the following distribution of road conditions: Excellent (55%), Very Good (17.5%), Good (12.5%), Poor (12.5%), and Very Poor (2.5%). These findings indicate that while most segments are in very good condition, there are critical points that require immediate attention. Maintenance recommendations include routine maintenance for roads in Excellent and Very Good condition, preventive maintenance for those in Good condition, rehabilitation for Poor conditions, and complete reconstruction for Very Poor conditions. Implementing these appropriate maintenance strategies is expected to enhance the functional performance of the pavements and extend the service life of the road sections. Keywords: road damage, flexible pavement, PCI, road maintenance, Sungai Penuh